Hepatitis Cvirus diversity and treatment outcomes in Benin: a prospective cohort study - Ahovègbé, Lucrèce; Shah, Rajiv; Kpossou, Aboudou Raïmi; Davis, Chris; Niebel, Marc; Filipe, Ana; Goldstein, Emily; Alassan, Khadidjatou S; Keke, René; Sehonou, Jean; Kodjoh, Nicolas; Gbedo, Sossa Edmond; et al. (The Lancet Microbe, 2024)
Background: 10 million people are chronically infected with the hepatitis C virus (HCV) in sub-Saharan Africa. The assessment of viral genotypes and treatment response in this region is necessary to achieve the WHO target of worldwide elimination of viral hepatitis by 2030. We aimed to investigate the prevalence of HCV genotypes and outcomes of treatment with direct-acting antiviral agents in Benin, a country with a national HCV seroprevalence of 4%. Methods: This prospective cohort study was conducted at two referral hospitals in Benin. Individuals were eligible for inclusion if they were seropositive for HCV and willing to consent to participation in the study; exclusion criteria were an inability to give consent or incarceration. Viraemia was conﬁrmed by PCR. The primary outcomes were to identify HCV genotypes and measure sustained virological response rates 12 weeks after completion of treatment (SVR12) with a 12-week course of sofosbuvir–velpatasvir or sofosbuvir–ledipasvir, with or without ribavirin. We conducted phylogenetic and resistance analyses after the next-generation sequencing of samples with a cycle threshold (Ct) value of 30 or fewer cycles. The in-vitro efﬁcacy of NS5A inhibitors was tested using a subgenomic replicon assay. Findings: Between June 2, 2019, and Dec 30, 2020, 148 individuals were screened for eligibility, of whom 100 were recruited prospectively to the study. Plasma samples from 79 (79%) of the 100 participants were positive for HCV by PCR. At the time of the study, 52 (66%) of 79 patients had completed treatment, with an SVR12 rate of 94% (49 of 52). 57 (72%) of 79 samples had a Ct value of 30 or fewer cycles and were suitable for whole-genome sequencing, from which we characterised 29 (51%) samples as genotype 1 and 28 (49%) as genotype 2. Three new genotype 1 subtypes (1q, 1r, and 1s) and one new genotype 2 subtype (2xa) were identiﬁed. The most commonly detected subtype was 2d (12 [21%] of 57 samples), followed by 1s (eight [14%]), 1r (ﬁve [9%]), 1b (four [7%]), 1q (three [5%]), 2xa (three [5%]), and 2b (two [3%]). 20 samples (11 genotype 2 and nine genotype 1) were unassigned new singleton lineages. 53 (93%) of 57 sequenced samples had at least two resistance-associated substitutions within the NS5A gene. Subtype 2d was associated with a lower-than-expected SVR12 rate (eight [80%] of ten patients). For one patient, with subtype 2b, treatment was not successful. Interpretation: This study revealed a high SVR rate in Benin among individuals treated for HCV with sofosbuvir– velpatasvir, including those with highly diverse viral genotypes. Further studies of treatment effectiveness in genotypes 2d and 2b are indicated.
Keywords: Hepatitis C virus (HCV); WHO; Treatment outcomes